Valuation of the U.S. stock market and the underestimation of risks before the 2008 financial crisis - Poleno, Kirill; Folprecht, Marek; Shabanov, Aleksandr; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2026)
This diploma thesis investigates whether valuation, macro-financial and sentiment indicators can provide early warning signals of severe stock market drawdowns. The study begins by reviewing theoretical foundations of equity valuation and behavioural biases that may lead to the mispricing of long-term risks. In the empirical section, a binary crash-event framework is applied to S&P 500 data, where crash definitions are based on forward peak-to-trough declines of 10%, 15% and 20% across multiple horizons. Several supervised learning models are evaluated using dependence-aware validation, probability calibration diagnostics and alarm metrics under limited alarm budgets. The results show that severe crashes over medium and long horizons exhibit measurable predictive structure, with simple valuation-based specifications performing competitively. While the models do not constitute a standalone forecasting tool, an illustrative risk-overlay suggests that such signals may assist in capital preservation. The findings confirm that valuation-driven indicators contain useful information about medium-term crash risk, while highlighting that performance is sensitive to horizon, evaluation design and event definition.
Vedoucí práce: Marek Folprecht
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses